Development of Local Content Teaching Material for the History of Wajo - Nurhikmah H; Muhammad Aris; Arismunandar Arismunandar; Sujarwo Sujarwo; Sukmawati Sukmawati (Yayasan Keluarga Guru Mandiri, 2022)
This study aims to develop local content reading books for the history of Wajo in an effort to add insight for educators and students from aspects of local history in Wajo Regency. The development of reading books follows 3 (three) stages from 4 (four) stages of development in the Four D development model. The research subjects consisted of validators as media experts and material experts, two history teachers as practitioners, and 60 students as a test subject. Data collection techniques used questionnaires and interviews, which were analyzed qualitatively and quantitatively. The results of the study showed that: students needed interesting history learning and motivated students to learn more about history so there was a need for reading books that support learning the history of local content in the Wajo Region. Local history was seen as more interesting because it was more contextual than national history. The development of teaching material for the history of Wajo was realized into a digital book (e-book) through the stages of validation and testing to determine the level of practicality. The validity of reading books was carried out by validation by teaching material experts, media experts and Wajo historians. The practicality of this reading book reaches 75.22% in the good category so that it is suitable for use and does not need revision.